2011
DOI: 10.5402/2011/392917
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Doped Alkali Earth Sulfide Phosphors for White-Light LEDs

Abstract: :Eu and SrS:Eu phosphors were synthesized by solid-state reaction. The effects of doping concentrations on luminescent properties of phosphors are investigated. The samples are excited using electroluminescent blue light emitting diode (460 nm) to examine them as potential coating phosphors for white-light LEDs. The excitation and emission spectra of these phosphors are broadband which can be viewed as the typical emission of Eu 2+ ascribed to the 4f-5d transitions. Because of their broadband absorption in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Some authors [8][9][10] have assigned the luminescence of the Sr 2 CeO 4 material to the charge transfer between Ce 4+ and O 2because the position and shape of the absorption band and the emission band width are characteristic for this type of transition. Some authors have observed that the strong luminescence of Sr 2 CeO 4 makes it potentially applicable as blue phosphor material in low pressure mercury vapor lamps [11] and FED [12,13] as well as other types of luminescence devices [14]. Following this observation, several studies about this luminescent material have been conducted, and some synthetic routes have been developed for the preparation of Sr 2 CeO 4 powders.…”
Section: Introductionmentioning
confidence: 97%
“…Some authors [8][9][10] have assigned the luminescence of the Sr 2 CeO 4 material to the charge transfer between Ce 4+ and O 2because the position and shape of the absorption band and the emission band width are characteristic for this type of transition. Some authors have observed that the strong luminescence of Sr 2 CeO 4 makes it potentially applicable as blue phosphor material in low pressure mercury vapor lamps [11] and FED [12,13] as well as other types of luminescence devices [14]. Following this observation, several studies about this luminescent material have been conducted, and some synthetic routes have been developed for the preparation of Sr 2 CeO 4 powders.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, metallic sulfides are one of the most researched materials due to possessing higher electrical conductivity and electrochemical activities through easy junction control and self‐ doping in photocatalytic applications [31], supercapacitors [32], light‐emitting diodes [33], gas detection systems [34] as well as lithium‐ion [35], and sodium‐ion batteries [36]. Among the metal sulfides, ZnS is one of the frequently studied nanomaterials owing to broadband energy, high electrochemical activity, electrical conductivity, abundant porous structure, the high density of active sites, and owning to various morphology according to the synthesis process [37–40].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the ability of shifting the peak emission of calcium sulfide doped with europium (CaS:Eu), a well-known red emitting inorganic phosphor material. CaS:Eu luminescent characteristics have been widely studied and used in a variety of applications such as, medical imaging [15,16], cell labeling [17], white-light-emitting diodes [18,19] and electroluminescent devices [20][21][22][23]. The red emission in CaS:Eu is originated from the Eu divalent state of ionization (Eu 2+ ) and its broad emission is caused by electron transition from the lower 4f 6 5d 1 state to the 4f 7 ground state [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, we present a study where the tuning is performed by adding oxygen anions reinforcing the idea that ALD can be used to modify the vicinity of the dopant elements. These materials fabricated by ALD can thus be used for applications where the fine color tuning is advantageous such as: red electroluminescent devices [20][21][22][23]28], white-light-emitting diodes [18,19] solar cells [29], and lasers [6,8,30].…”
Section: Introductionmentioning
confidence: 99%